Microsurgical reconstruction of the breast: ′The versatile lower abdomen′ - Ramakrishnan Venkat (Indian Journal of Plastic Surgery)
Since the first reported use of lower abdominal tissue from the lower abdominal skin and fat by Hans Holmstrom in 1979, there have been over 300 publications on this subject. The refinements have been aimed at the limitation of donor morbidity and to allow a predictable success of the transfer. This article analyses the landmarks and highlights the key developments in this area. The more recent development in this area - the Deep Inferior Epigastric Perforator flap is discussed.